Uncovering the impact of metals on the formation and physicochemical properties of fat, oil and grease deposits in the sewer system - Yusuf, Hamza Hassan; Roddick, Felicity; Jegatheesan, Veeriah; Jefferson, Bruce; Gao, Li; Pramanik, Biplob Kumar (Elsevier, 2024)
The deposition of fats, oil, and grease (FOG) in sewers reduces conveyance capacity and leads to sanitary sewer overflows. The major contributing factor lies in the indiscriminate disposal of used cooking oil (UCO) via kitchen sinks. While prior investigations have mostly highlighted the significance of Ca2+ from concrete biocorrosion, the influence of common metal ions (e.g., Mg2+, Na+, K+) found in kitchen wastewater on FOG deposition has received limited attention in the existing literature. This study aimed to elucidate the roles of Ca, Mg, Na and K in FOG deposition in sewers and examine the influence of metal ions, fat/oil sources, and free fatty acids (FFAs) on the physicochemical and rheological properties of FOG deposits. To examine FOG deposit formation, synthetic wastewater containing 0.1 g/L of each metal ion was mixed with 40 mL of fat/oil and agitated for 8 h. Following FOG deposition, three distinct phases were observed: unreacted oil, FOG deposit and wastewater. The composition of these phases was influenced by the composition of metal ions and FFA in the wastewater. Mg produced the highest amount of FOG of 242.5 ± 10.6 mL compared to Ca (72.5 ± 3.5 mL) when each FFAs content in UCO was increased by 10 mg/mL. Molar concentration, valency and the solubility of metal ion sources were identified to influence the formation of FOG deposits via saponification and aggregation reaction. Furthermore, Fourier-Transform Infrared spectroscopy indicated that the FOG deposits in this study were similar to those collected from the field. This study showed that the use of Mg(OH)2 as a biocorrosion control measure would increase FOG deposition and highlights the need for a comprehensive understanding of its roles in real sewage systems.
Keywords: 41 Environmental Sciences; 40 Engineering; 4104 Environmental Management; Corrosion; FOG deposit; Fatbergs; Free fatty acid; Mg(OH)(2); Sewer; Environmental Sciences; Meteorology & Atmospheric Sciences